2021
DOI: 10.2147/ccide.s331426
|View full text |Cite|
|
Sign up to set email alerts
|

Microleakage Evaluation in Class V Cavities Restored with Five Different Resin Composites: In vitro Dye Leakage Study

Abstract: Purpose Restorative materials and techniques have improved the clinical success of a variety of restorative procedures. Despite these new improvements, microleakage remains one of the leading causes of restoration failure and may lead to postoperative sensitivity, enamel microcracks, marginal staining, discoloration, recurrent caries, and deformation of teeth. This study evaluated microleakages of five recent resin composites in class V cavities. Materials and Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Consistency between in vivo and in vitro studies, taking into account the structural phenomena to be observed, ensures a result that corresponds to real conditions observable in clinical practice [ 12 ]. Due to the lack of evidence and protocols, the authors decided not to sterilise the teeth before restoration, as this could alter the tooth structures, especially the collagen fibres, which are crucial for the success of the adhesive procedures [ 14 ]. A comparison of in vivo and in vitro data revealed that the most valid method for analysing the stability of adhesion over time is sample ageing, a process that makes the results of microleakage and marginal adaptation more clinically relevant [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistency between in vivo and in vitro studies, taking into account the structural phenomena to be observed, ensures a result that corresponds to real conditions observable in clinical practice [ 12 ]. Due to the lack of evidence and protocols, the authors decided not to sterilise the teeth before restoration, as this could alter the tooth structures, especially the collagen fibres, which are crucial for the success of the adhesive procedures [ 14 ]. A comparison of in vivo and in vitro data revealed that the most valid method for analysing the stability of adhesion over time is sample ageing, a process that makes the results of microleakage and marginal adaptation more clinically relevant [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These measurements were taken for both sides of the restoration (right and left) and the highest value was considered as microleakage. Given the 4 mm depth of all cavities, the author used the following formula to calculate the actual microleakage [ 14 ]: %MicroLeak = (AB/4 mm) × 100 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, nanohybrid composite resins contain 0.005 to 0.01-nm particles and provide good aesthetic as well as satisfactory physical, chemical, and biological properties which are deemed necessary for increased longevity of the restoration. 16 The long-term success of composite restorations is dependent on the resistance of different components of this complex system such as different surfaces and interfaces, to stress and deformation. 17 Incorrect stress distribution in restorations can add to the stress caused by polymerization shrinkage, so, finite element analysis (FEA) was used to quantify the biomechanical behaviors of complex structures.…”
Section: Discussionmentioning
confidence: 99%
“…A falha dessas restaurações do tipo Classe V parece ser uma ocorrência comum na prática clínica e pode ter várias implicações envolvidas, tais como características morfológicas da região e a desão à dentina ou cemento. Nesse sentido, podem ocorrem microinfiltrações que permitem a passagem de bactérias por esse espaço entre a parede cavitária e a resina composta, podendo levar a hipersensibilidade, cárie secundária, patologia pulpar e, eventualmente, falha das restaurações (Bajabaa et al, 2021).…”
Section: Revisão Da Literaturaunclassified
“…No que se refere a vitalidade pulpar, presença de lesões de cárie em margem de restauração e integridade marginal, apenas uma lesão do mesmo grupo referido acima apresentou presença de lesão de cárie e conceito CHARLIE na integridade marginal e consequentemente, comprometimento de vitalidade pulpar (encaminhado para tratamento endodôntico), não podendo ser feita nenhuma correlação com o tratamento realizado. Nesse sentindo, existem vários fatores que podem levar à falha da restauração, tais como: o tamanho e forma da cavidade, tipo de substrato e posição da margem, material restaurador e procedimento de colocação e polimerização (Bajabaa et al, 2021).…”
Section: Avaliação Da Pigmentação Marginalunclassified